The relationship between trait mindfulness and subjective wellbeing of kindergarten teachers: The sequential mediating role of emotional intelligence and self-efficacy - Pan, Baocheng; Fan, Shiyi; Wang, Youli; Li, You (Frontiers in Psychology, 2022)
This study explored the relationship between emotional intelligence and self-efficacy in trait mindfulness and subjective well-being. The present study used the five facet mindfulness questionnaire, emotional intelligence scale, general self-efficacy scale and subjective well-being scale to measure 323 kindergarten teachers in China. The study found that trait mindfulness can directly predict subjective well-being (β = 0.257, p < 0.001). Emotional intelligence could mediate the relationship between trait mindfulness and subjective well-being (β = 0.165, p = 0.006). Self-efficacy could mediate the relationship between trait and subjective well-being (β = 0.078, p = 0.032). In addition, emotional intelligence and self-efficacy played a sequential mediating role between trait mindfulness and subjective well-being (β = 0.072, p = 0.005). This study revealed the relationship between kindergarten teachers’ trait mindfulness and subjective well-being through structural equation modeling and understood its role path, enriching the research on the Chinese preschool teacher group in the field, and providing a literature reference for the international community to understand the Chinese kindergarten teacher group. At the same time, the study also has some limitations, such as the use of a cross-sectional design method, a relatively single method, and the impact of COVID-19. However, we believe that this study will further enrich the research literature on the relationship between trait mindfulness and subjective well-being among Chinese kindergarten teachers and provide references for practice.